2017
DOI: 10.1093/mnras/stx513
|View full text |Cite
|
Sign up to set email alerts
|

XMM–Newton observation of MV Lyr and the sandwiched model confirmation

Abstract: We present spectral and timing analyses of simultaneous X-ray and UV observations of the VY Scl system MV Lyr taken by XMM-Newton, containing the longest continuous X-ray+UV light curve and highest signal-to-noise X-ray (EPIC) spectrum to date. The RGS spectrum displays emission lines plus continuum, confirming model approaches to be based on thermal plasma models. We test the sandwiched model based on fast variability that predicts a geometrically thick corona that surrounds an inner geometrically thin disc. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 54 publications
9
26
1
Order By: Relevance
“…Finally, Borisov (1992) and Skillman et al (1995) together with Kraicheva et al (1999) found a QPO at a period near 47 minutes. The corresponding frequency of log(f /Hz) = -3.45 is in perfect agreement with one PDS component detected by Scaringi et al (2012a) in the optical Kepler data and by Dobrotka et al (2017) in the X-ray XMM-Newton light curve. This power excess is also seen in the simulations (Fig.…”
Section: Possible Contamination and Other Detectionssupporting
confidence: 81%
See 3 more Smart Citations
“…Finally, Borisov (1992) and Skillman et al (1995) together with Kraicheva et al (1999) found a QPO at a period near 47 minutes. The corresponding frequency of log(f /Hz) = -3.45 is in perfect agreement with one PDS component detected by Scaringi et al (2012a) in the optical Kepler data and by Dobrotka et al (2017) in the X-ray XMM-Newton light curve. This power excess is also seen in the simulations (Fig.…”
Section: Possible Contamination and Other Detectionssupporting
confidence: 81%
“…If the variability is generated by the corona radiating hard X-rays, the optical Kepler data is a result of the reprocessing of the X-rays, and the corresponding PDS component must be detected in X-rays too. This interpretation was confirmed by XMM-Newton observations (Dobrotka et al 2017) where two highest PDSs components were detected.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…This approach is suitable to study quasi periodic oscillations (QPOs) or red noise. We estimated the PDS as in Dobrotka et al (2017), i.e. we split the light curve into n div subsamples (subdivision in time ranges), then we calculated periodograms in log-log space for every subsample, averaged them and finally binned the data in equally spaced bins if a minimum number of points per bin is fulfilled (otherwise the bin is larger).…”
Section: Timing Analysismentioning
confidence: 99%